Infektiöse Endokarditis - Knebel, Fabian; Frumkin, David; Flachskampf, Frank A. (DMW - Deutsche Medizinische Wochenschrift, 2019)
Infective endocarditis is a severe, mostly bacterial disease characterized by high mortality and morbidity. Both diagnosis and therapy are difficult, and mortality rates have not improved over decades. We review diagnostic and management problems, the disease's modern face in the era of widespread cardiac implants and valve interventions, and current diagnostic and therapeutic recommendations.
Keywords: Endokarditis; transösophageale Echokardiografie; Antibiotikaprophylaxe; Endokarditis-Team; Herzklappenprothesen